Pengaruh Dimensi Kepemimpinan Transformasional terhadap Kepuasan Kerja dan Komitmen Organisasional: Studi Kasus pada Dosen Perguruan Tinggi Swasta - Jumiran Jumiran; Dewiana Novitasari; Yunianto Agung Nugroho; Didi Sutardi; Ipang Sasono; Masduki Asbari (EduPsyCouns: Journal of Education, Psychology and Counseling, 2020)
This study aimed to measure the effect of dimensions of transformational leadership (i.e. idealized influence, inspirational motivation, intellectual stimulation and individualized consideration) on organizational commitment of the the lecturers of a privat higher education institution in Tangerang which are mediated by job satisfaction. Data collection was done by simple random sampling to 151 population of lecturers. The returned and valid questionnaire results were 102 samples. Data processing was used SEM method with SmartPLS 3.0 software. The results of this study concluded: first, the dimensions of transformational leadership: idealized influence, intellectual stimulation and individualized consideration have positive and significant effect on job satisfaction, except inspirational motivation. Second, the dimensions of transformational leadership: idealized influence, inspirational motivation, and individualized consideration have not significant effect on organizational commitment, except intellectual stimulation. Third, job satisfaction have a positive and significant effect on organizational commitment. Fourth, the dimensions of transformational leadership: idealized influence, intellectual stimulation and individualized consideration have positive and significant effect on organizational commitment through job satisfaction as mediation, but inspirational motivation have not significant effect on organizational commitment through job satisfaction as mediation. This study proposed a model for building the organizational commitment among the lecturers of a privat higher education institution in Tangerang through enhancing transformational leadership with job satisfaction as a mediator. This research could pave the way to improve the lecturer readiness in facing the era of education 4.0.